2012
DOI: 10.1242/dev.072561
|View full text |Cite
|
Sign up to set email alerts
|

Sim2 prevents entry into the myogenic program by repressing MyoD transcription during limb embryonic myogenesis

Abstract: SUMMARYThe basic helix-loop-helix transcription factor MyoD is a central actor that triggers the skeletal myogenic program. Cellautonomous and non-cell-autonomous regulatory pathways must tightly control MyoD expression to ensure correct initiation of the muscle program at different places in the embryo and at different developmental times. In the present study, we have addressed the involvement of Sim2 (single-minded 2) in limb embryonic myogenesis. Sim2 is a bHLH-PAS transcription factor that inhibits transc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 56 publications
0
30
0
Order By: Relevance
“…MyoD is likely to drive MPCs toward terminal differentiation, and, interestingly, its expression in the ventral forelimb was recently reported to be temporally controlled by Sim2 (Havis et al 2012). Consistent with this, a Myogenin-lacZ transgene is not expressed in MyoD À/À limbs, whereas some expression occurs in Myf5 À/À limbs (Kablar et al 2003).…”
Section: Myf5 and Myod May Define Different Myogenic Stages In Limb Mpcsmentioning
confidence: 69%
“…MyoD is likely to drive MPCs toward terminal differentiation, and, interestingly, its expression in the ventral forelimb was recently reported to be temporally controlled by Sim2 (Havis et al 2012). Consistent with this, a Myogenin-lacZ transgene is not expressed in MyoD À/À limbs, whereas some expression occurs in Myf5 À/À limbs (Kablar et al 2003).…”
Section: Myf5 and Myod May Define Different Myogenic Stages In Limb Mpcsmentioning
confidence: 69%
“…In situ hybridization analyses of mouse adult tendons were processed using the mouse Egr1 and Col1a1 digoxigenin-labeled mRNA probes, as previously described for mouse embryos (14,62), followed by nuclear fast red staining. Rat Achilles tendons manipulated with C3H10T1/2-EV or C3H10T1/2-EGR1 cells were fixed in 4% paraformaldehyde, processed for cryostat sections, and stained with H&E. Tendon-like constructs from control C3H10T1/2 or C3H10T1/2-EGR1 cells were fixed in 4% paraformaldehyde, transverse paraffin sectioned, and immunostained with the Ki67 antibody (Ab15580; Abcam) or with the polyclonal antibody against type I collagen (Ab292; Abcam).…”
mentioning
confidence: 99%
“…ChIP assays were performed as previously reported (62). Achilles tendons from 100 postnatal mice were homogenized using a mechanical disruption device (Lysing Matrix A, Fast Prep MP1, 3 × 30 seconds; MP Biomedicals).…”
mentioning
confidence: 99%
“…Although most bHLH-PAS factors are activators of transcription, Sim2 acts as a transcriptional repressor in mammalian cells (9,35). In addition to its role in CNS development and mental retardation in DS, SIM2 is also involved in muscle and limb development (10,16,21). Recently, several studies have reported that, depending on the origin of tumors, SIM2 may act as a suppressor or stimulator on their growth and development (14,15,28,29).…”
Section: Discussionmentioning
confidence: 99%